Customer retention in Malaysia banks: the effect of relationship marketing, service quality, price, and mediation of satisfaction - Chim, Weng Kong (2022)
A customer retention strategy is a must for any bank that wishes to remain in this competitive banking. As mentioned in past research, retaining customers is worth more than attracting new ones. The purpose of retaining customers is to maintain a customer base for repeat purchases and revenue-generating. Banks' merger exercise has created a more extensive customer base that allows the banks to cross-sell their products. However, some banks' performance fluctuates. The worst scenario is that lowerranking banks can perform better than the higher-ranking and larger banks. Therefore, this study aims to understand how to meet the customers' expectations with satisfaction through relationships by building up customer relationships through relationship marketing. Establishing a long-term relationship is a way for the banks to provide service quality, whether human-related or non-human related. Satisfaction would be the mediator to meeting customers' expectations, although service quality perceptions differ. Another variable contributing to this study is the banks' price (interest) to customers. A slight price difference contributes to a massive difference between the banks and customers. A quantitative research was conducted to obtain the research result by distributing questionnaires to randomly picked banks' customers in three areas, namely Taiping, Ipoh, and Teluk Intan. One hundred twenty-nine questionnaires were accepted and analysed with SmartPLS software. The results indicate a positive relationship between relationship marketing and service quality towards customer retention. Both are mediated with satisfaction and support. However, the relationship between price and customer retention is not supported nor mediated by satisfaction. With this outcome, the chances of customers moving to competitors are very high if the competitors offer a better price. Since price is not supported in this research, any future research on customer retention in banks should be conducted from the standpoint of banks' operating or management expenses. Thus, banks can also re-look into the pricing or interest strategy.